Blockade of Exosome Release Suppresses Atrial Fibrillation by Alleviating Atrial Fibrosis in Canines With Prolonged Atrial Pacing - Yao, Yajun; He, Shanqing; Wang, Youcheng; Cao, Zhen; Liu, Dishiwen; Fu, Yuntao; Chen, Huiyu; Wang, Xi; Zhao, Qingyan (Frontiers in Cardiovascular Medicine, 2021)
Background: Clinical studies have shown that exosomes are associated with atrial fibrillation (AF). However, the roles and underlying mechanisms remain unclear. Hence, this study aimed to investigate the function of exosomes in AF development. Methods: Twenty beagles were randomly divided into the sham group (n=6), the pacing group (n=7), and the pacing+GW4869 group (n=7). The pacing and the GW4869 group underwent rapid atrial pacing (450 beats/min) for 7 days. The GW4869 group received intravenously GW4869 injection (an inhibitor of exosome biogenesis/release,0.3mg/kg, once a day) during the pacing. Electrophysiological measurements, Transmission electron microscopy, Nanoparticle tracking analysis and Western blotting, RT-PCR, Masson's staining, and immunohistochemistry were performed in this study. Results: Rapid atrial pacing increased the releases of plasma and atrium exosomes. GW4869 treatment markedly suppressed AF induction and reduced the release of exosomes. After 7 days of pacing, the expressions of transforming growth factor-β1 (TGF-β1), collagen Ⅰ/Ⅲ and matrix metalloproteinases were enhanced in atrium, the levels of microRNA-21-5p (miR-21-5p) were upregulated in both plasma exosomes and atrium, while tissue inhibitor of metalloproteinase 3(TIMP3), a target of miR-21-5p, showed a lower expression in atrium. Administration of GW4869 abolished these effects. Conclusions: Blockade of exosomes release with GW4869 suppressed AF through alleviating atrial fibrosis, which was probably related to pro-fibrotic miR-21-5p enriched in exosomes and its downstream TIMP3/TGF-β1 pathway.